PERANAN UNIT IDENTIFIKASI DIREKTORAT RESERSE KRIMINAL UMUM POLISI DAERAH RIAU DALAM MENGUNGKAP PELAKU TINDAK PIDANA PEMBUNUHAN BERENCANA MENGGUNAKAN METODE DACTILOSCOPY - Willa Maysela F; Mukhlis R; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Developments in science and technology can give birth to a crime that varied both in quality and quantity in this particular crime of premeditated murder, as one of the functions of the technical assistance in disclosing the perpetrators of murder scientifically Identification Unit still not up or in other words not managed to uncover the perpetrators of these crimes by using the method Dactiloscopy (fingerprint identification).